Adenocarcinoma and dysplasia in barrett`s esophagus: critical analysis of risk factors and of surveillance protocols - Gallon, Eduardo (2024)
BACKGROUND: Identification of epidemiological risk factors in Barrett's esophagus resulting in dysplasia and adenocarcinoma and its impact on prevention and early detection. AIMS: To evaluate epidemiological risk factors involved in the development of dysplasia and adenocarcinoma from Barrett's esophagus in a specific population. To critically analyze the surveillance period, aiming to individualize follow-up time according to identified risks. METHODS: A retrospective case-control study in a tertiary center with patients diagnosed and followed up for Barrett's esophagus. Patients with Barrett's esophagus who developed adenocarcinoma and/or dysplasia were compared to those who did not, considering variables such as sex, age, smoking status, Body mass index, ethnicity, and Barrett's extension. Logistic regression was performed to measure the odds ratio between risk factors for the outcome of adenocarcinoma and of dysplasia. The presence of epidemiological risk factors in this population was correlated with the time to develop adenocarcinoma from metaplasia. RESULTS: There was a statistically significant difference between the variables smoking status, race, sex, Barrett's esophagus extension, and age in the group with adenocarcinoma compared to the group without adenocarcinoma; smokers and former smokers had a 4.309 times higher risk of developing adenocarcinoma; the extension of Barrett's esophagus increased the risk by 1.193 times for each centimeter. In dysplasia group, the variables smoking status, Barrett's extension, and age were statistically significant; the extension of Barrett's esophagus increased the risk of dysplasia by 1.128 times for each centimeter, and age increased the risk by 1.023 times for each year. Patients without risk factors did not develop adenocarcinoma within 12 months, even with prior dysplasia. CONCLUSIONS: The study confirmed a higher risk of developing dysplasia and adenocarcinoma in specific epidemiological groups, allowing for more cost-effective monitorization in patients with Barrett's esophagus.